Filsafat dan Pendidikan : Kontribusi Pemikiran Islam dalam Pengembangan Karakter - Raihan Difari; Muhammad Hisyam; Herlini Puspita Sari (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to find out how much contribution Islamic thinkers have made in the field of character development and how big their influence is today. This research uses the library research method, namely the approach used to collect and analyze data from various literary sources such as books, journals and documents. The research results show that Islamic figures have made a major contribution to character development in the world of education. The results of the research show that Islam has a major contribution to character development in the world of education, one of the proofs of which can be seen from the purpose of the Prophet Muhammad SAW who was sent to this earth, namely to perfect morals.